CCL17‐CCR4 axis contributes to the onset of vitiligo in mice. Issue 3 (2nd June 2021) - Li, He; Wang, Congpin; Li, Xiaoqing; Kong, Yinghui; Sun, Weiguo
Abstract: Background: Destruction of melanocytes mediated by autoimmunity is currently believed as the main cause of vitiligo. This article aims to identify the role of CC chemokine ligand 17 (CCL17)–CC chemokine receptor 4 (CCR4) axis in vitiligo and provide new possibilities for the clinical treatment of vitiligo. Methods: A total of 30 patients with vitiligo from Affiliated Huaian No. 1 People's Hospital of Nanjing Medical University were recruited based on the inclusion and exclusion criteria. Trephine was used to obtain skin samples from the lesion area and its surrounding normal areas, and the expression levels of CCL17, CCR4, Tbx21, Eomes, and Blimp1 were determined by quantitative reverse transcription polymerase chain reaction. Vitiligo mouse model was established by adoptively transferring CFP‐PMEL CD8+ T cells into sublethally irradiated Krt14‐Kitl* mice. Recipient mice received intraperitoneal injection of 1 × 10 6 plaque‐forming units of rVV‐hPMEL on the same day of transfer. The degree of depigmentation was scored blindly by one observer 5 weeks after vitiligo induction. CFP‐PMEL CD8+ T cells migration to skin, draining lymph nodes, spleen, and blood were detected by flow cytometry. CCR4 blockade was performed by intraperitoneal injection of neutralizing antibody. Results: The expression levels of CCL17, CCR4, Tbx21, Eomes, and Blimp1 in skin lesions were significantly increased compared with that in surrounding normal areas. CCL17 −/− and CCR4 −/− mice exhibited significantly lower disease scores than WT mice. The CFP‐PMEL CD8+ T cells accumulation was significantly decreased in the skin of CCL17 −/− and CCR4 −/− mice, but was not changed in draining lymph nodes, spleen, and blood. Administration of CCR4 neutralizing antibody decreased the degree of depigmentation and the recruitment of CFP‐PMEL CD8+ T cells to the skin, while keeping the number of T cells in draining lymph nodes unchanged. Conclusion: Targeting CCL17‐CCR4 axis might inhibit T cell migrating to skin and alleviate vitiligo progression. Abstract :